Prevalence of under Nutrition and Associated Factors among Khat Chewers in Khat Chewing Shops at Gulalle Sub City, Addis Ababa, Ethiopia - Tesfaye Girma Legesse ,; Debela Gemeda Bedane, (Journal of Pharmacy and Nutrition Sciences, 2016)
There is studies limitation regarding the effect of khat chewing on nutritional status. Community based comparative cross-sectional study had been conducted from March to June, 2015; with cluster sampling and systematic random sampling techniques for khat chewers and non-khat chewers respectively. The data was collected by using interview administered questionnaire, observation and weight scale measurement among 504 study participants.The study revealed that from entire khat chewers 52(20.5%) of them and of non-khat chewers 34(13.5%) of them were underweight. Khat chewers were 2.102 times more likely underweight compared to those non-khat chewers. khat chewers who had meal twice per day were 2.856 time more likely underweight. Khat chewers who used animal and animal products as their main meal component daily were 0.413 times less likely to be underweight; Whereas the odds of underweight was 26% times less likely among khat users who intake two liters of fluid per chewing session. In other case, those who chewed khat for 2-3 hours per session were 0.231 times less likely to be underweight.Under nutrition is a public nutritional status problem in which khat chewers are more affected. Khat chewing conditions and meal conditions including amount of fluid consumed per chewing session are factors that affect the nutritional status of the khat chewers. Minimizing amount of khat consumed per session, shortening of khat chewing session length and increasing amount of fluid intake more than two liters per chewing session and nutritional management with nutritionist advices are important points.